Smoking and blood DNA methylation: an epigenome-wide association study and assessment of reversibility. Issue 4 (2nd April 2020) - Dugué, Pierre-Antoine; Jung, Chol-Hee; Joo, Jihoon E; Wang, Xiaochuan; Wong, Ee Ming; Makalic, Enes; Schmidt, Daniel F; Baglietto, Laura; Severi, Gianluca; Southey, Melissa C; English, Dallas R; Giles, Graham G; et al.
ABSTRACT: We conducted a genome-wide association study of blood DNA methylation and smoking, attempted replication of previously discovered associations, and assessed the reversibility of smoking-associated methylation changes. DNA methylation was measured in baseline peripheral blood samples for 5, 044 participants in the Melbourne Collaborative Cohort Study. For 1, 032 participants, these measures were repeated using blood samples collected at follow-up, a median of 11 years later. A cross-sectional analysis of the association between smoking and DNA methylation and a longitudinal analysis of changes in smoking status and changes in DNA methylation were conducted. We used our cross-sectional analysis to replicate previously reported associations for current (N = 3, 327) and former (N = 172) smoking. A comprehensive smoking index accounting for the biological half-life of smoking compounds and several aspects of smoking history was constructed to assess the reversibility of smoking-induced methylation changes. This measure of lifetime exposure to smoking allowed us to detect more associations than comparing current with never smokers. We identified 4, 496 cross-sectional associations at P < 10 −7, including 3, 296 annotated to 1, 326 genes that were not previously implicated in smoking-associated DNA methylation changes at this significance threshold. We replicated the majority of previously reported associations (P < 10 −7 ) for current and former smokers. In our data, we observed for former smokers a substantial degree of return to the methylation levels of never smokers, compared with current smokers (median: 74%, IQR = 63-86%), corresponding to small values (median: 2.75, IQR = 1.5–5.25) for the half-life parameter of the comprehensive smoking index. Longitudinal analyses identified 368 sites at which methylation changed upon smoking cessation. Our study demonstrates the usefulness of the comprehensive smoking index to detect associations between smoking and DNA methylation at CpGs across the genome, replicates the vast majority of previously reported associations, and quantifies the reversibility of smoking-induced methylation changes.